Reflective Thinking Profile of Physics Teacher Prospective Students through Nuclear Physics Learning using Virtual Laboratory - Sinensis, Arini Rosa; Firdaus, Thoha (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2023)
Virtual Laboratory is a platform that helps students carry out practicum-based learning both independently and in groups. Nuclear physics is an abstract concept that discusses atomic nuclei, atomic nuclei decay, radioactivity which allows in practice to use virtual. The purpose of this study was to determine the level of students' reflective thinking skills after using the virtual lab in the nuclear physics course. The method used is descriptive quantitative. The data collection technique used a modified Kember reflective questionnaire with 24 statement items consisting of aspects of habitual action, understanding, reflection, and critical reflection. The research subjects were 15 prospective physics teacher students. The results showed that the level of reflective ability: habitual action (72.7%), understanding (89.3%), reflection 76.9% and critical reflection (67.87%) means that all levels are in the high category. These results explain that the profile of students' reflective thinking abilities is in the high category after learning nuclear physics using a virtual laboratory.